Investigation of residual stresses in sapphire plates after grinding and polishing - Budnikov, A.T.; Vovk, E.A.; Kanishchev, V.N.; Krivonogov, S.I. (Functional Materials, 2012)
The method of flexure determination was used to investigate the dependence of residual stresses on the depth of damaged layer in sapphire plates with a diameter of 100 mm after grinding and polishing. The flexure was determined from nonflatness of the control side of the plate using an interferometer of IT-200 type. The layer damaged in the process of grinding or polishing (of the tested side of the plate) was removed by chemico-mechanical polish. The removed value was established to an accuracy of 0.1 mg by weighing the plate before and after the treatment. The plate flexure was found to diminish with each removed layer, and to disappear after removal of 7 µm and 0.4 µm thick layer of the ground and polished samples, respectively. The most essential deformation caused by residual stresses was observed in the layers of the ground and polished plates with a thickness of 0.12-0.24 µm and 0.09-0.14 µm, respectively.